Corporate reputation and the future cost of equity - Benjamin Pfister; Manfred Schwaiger; Tobias Morath (Business Research, 2020)
Corporate reputation is an important management objective, bearing the potential to create sustainable competitive advantage, and many scholars have studied its impact on firm performance. However, its effect on the cost of equity has only recently begun to attract the attention of academic research. Empirical evidence is scarce, and the results are inconclusive. Applying a validated measure of reputation, we scrutinize its impact for a set of German blue-chip companies between 2005 and 2011. We show that higher levels of reputation are associated with a lower future cost of equity. While reputation improvements are not followed by a measurable short-term effect, reputational damages lead to a significant increase in the future cost of equity within 6~months. We interpret our findings against the backdrop of the previous studies, offering several explanations for diverging results.
Keywords: G32; M14; D83; 650; Corporate reputation; Corporate risk; Cost of equity; Information asymmetry; Reputational damages; Intangible assets